Macroeconomics and Monetary Economics - 1: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
Demand and supply side assessment are the two foremost important components of energy management and planning. Unfortunately, for the past twenty years Pakistan is confronting extremely serious issues with energy management such as electricity followed by institutional incompetence and lack of policy response. This is due to the fact that the country neither has long term energy plans nor short-term solutions to deal with energy crisis. This study outlines overall consumption of electricity and forecasting its various components. The interminable crisis of electricity affects all sectors of economy. The study deals with this particular aspect and applies Holt-winter and ARIMA models for the forecasting. The outcomes of both the models suggest that ARIMA model is more reliable for forecasting as compared to Holt-winter model. Estimated results affirm the tendency of increasing demand in all the indices which show an alarming position in future. Household sector will have the highest energy demand in 2030, followed by industrial sector. Thus, due to the ever increasing demand of electricity energy, government should initiate different renewable sources of power production such as hydal and solar energy to overcome the shortfall of electricity energy as well as sustainability in economy.